2021
DOI: 10.1007/s12144-021-01992-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived organizational support on employee creativity: The mediating role of work engagement

Abstract: The aim of this study is to examine the relationship between perceived organizational support and employee creativity mediated by work engagement. We report the results from a questionnaire survey on a sample of 492 professional employees (219, 44.51% females and 273, 55.49% males) employed in two major industries in the United Kingdom.Our findings based on regression analysis show that work engagement mediates the relationship between perceived organizational support and employee creativity. In summary, emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 103 publications
4
27
0
Order By: Relevance
“…This study examined the relationship between POS and the creative performance of the employees by conducting field research on a public sector body. The findings indicated that there is a strong positive relationship between perceived organisational support in its considered dimensions and the creative performance of employees, which are consistent with the findings of Aldabbas et al (2021) between the two. This discrepancy shows the importance of the present study to remove some of the ambiguity surrounding this relationship, as well as the need to conduct more research in this field.…”
Section: H4 Testingsupporting
confidence: 87%
“…This study examined the relationship between POS and the creative performance of the employees by conducting field research on a public sector body. The findings indicated that there is a strong positive relationship between perceived organisational support in its considered dimensions and the creative performance of employees, which are consistent with the findings of Aldabbas et al (2021) between the two. This discrepancy shows the importance of the present study to remove some of the ambiguity surrounding this relationship, as well as the need to conduct more research in this field.…”
Section: H4 Testingsupporting
confidence: 87%
“…The Relationship Between Work Engagement and Job Performance Work engagement is a positive and complete emotional and cognitive state related to work, associated with the characteristics of persistence and dispersion (Li and Ling, 2007;Aldabbas et al, 2021). Based on findings from previous studies, there remains debate regarding the relationship between job involvement and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the formation of creativity not only requires individuals to be motivated to try, but also requires individuals to have the confidence and ability to break through, previous studies have mostly analyzed the factors influencing creativity at a single "willingness" level, such as calling 68 and work engagement. 16,17 This study further enriches the exploration of creativity influencing mechanisms by exploring the formation of creativity at both the "willingness" and "ability" levels.…”
Section: Theoretical Contributionmentioning
confidence: 90%
“…15 In the digital era, science-technology talents with digital thinking can not only objectively view the organization's attitude toward them, as well as their status and value in the organization, and improve their emotional attachment to the organization, but they can also dialectically and critically view the vast amount of digital information, explore potentially useful information, improve resource utilization efficiency and innovation effectiveness, and enjoy innovative thinkers. The existing literature was primarily based on stressors, 16 work engagement, 17 and other perspectives to investigate the influencing factors of creativity without introducing elements of the digital era into the context of the digital era, and there were few studies on the creativity of science-technology talents, as well as the mechanism of the role of perceived organizational support and creativity in the digital environment.…”
Section: Introductionmentioning
confidence: 99%